Procedure proposal for determining the maintenance policy out of the criticality analysis of productive equipment in sugar mills - Alfonso Llanes, Aramis; Granela Martín, Hugo; Hernández Pascual, Kely (Centro Azúcar Journal, 2008)
The paper outlines a procedure based on the level of criticality of the productive equipment in sugar mills, a proposal defined by the selection of the main variables that characterize its environment, determines the maintenance strategy recommended, all focused to achieve a significant improvement in the management of maintaining them. The proposal stresses the insertion of innovative methods to assess some of the variables used and a group of meanings in the case of continuous production environments, being demonstrated the possibility to determine the most appropriate maintenance variant for each equipment in the sugar mill combining the classification of their failures and their criticality level.